ARHITECTURA BIBLIOTECILOR PUBLICE: TEORII ŞI REALIZĂRI PRACTICE - GOIAN, Conf. univ. dr., Catedra Biblioteconomie şi Asistenţă Informaţională a USM, Natalia; BERNIC, director al Bibliotecii Publice „D. Cantemir”, Ungheni, Victoria (BIBLIOPOLIS, 2020)
The subject of the article The public library’s arhitecture: theory and practices is actual and indispensable to the organization of library spaces as public spaces. The effi ciency of library activities can be ensured by structuring the spaces in according with the standards valid for this type of construction. The authors, dr. Natalia Goian and Victoria Bernic, analyse the library of the point of view of its spaces, underlinening the share of the public space and the situation in the public libraries of the country. The article includes also a case study: The effi ciency of the use of County Public Library Dimitrie Cantemir from Ungheni, which can be a model of space’s evaluation for the public libraries of the Republic of Moldova.